Sudden Infant Death syndrome - Mirian; M. (M.Sc) (حیات, 2002)
The term: SID syndrome applies to sudden and unexpected death of the infant for which no diagnostic fetal factor has been found. It is also applied to sudden death of a less than one year old baby, the cause is not recognizable after complete post mortem study, and review of disease records. Such a death will be a very bitter and sorrowful experience for the family, therefor the nurses are bound to support the family both mentally and spiritually.